2013
DOI: 10.1111/nyas.12039
|View full text |Cite
|
Sign up to set email alerts
|

Targeting phosphoinositide 3‐kinase δ for the treatment of respiratory diseases

Abstract: Asthma and chronic obstructive pulmonary disease (COPD) are characterized in their pathogenesis by chronic inflammation in the airways. Phosphoinositide 3-kinase δ (PI3Kδ), a lipid kinase expressed predominantly in leukocytes, is thought to hold much promise as a therapeutic target for such inflammatory conditions. Of particular interest for the treatment of severe respiratory disease is the observation that inhibition of PI3Kδ may restore steroid effectiveness under conditions of oxidative stress. PI3Kδ inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 14 publications
0
54
0
Order By: Relevance
“…Especially NE and MMP-9 are targeted, together with neutrophil infiltration. For example, inhibiting PI3Kd decreases neutrophil infiltration in murine models of acute lung damage, and might therefore also be a target for the treatment of COPD [128]. However, it seems that neutrophil signaling pathways are altered in COPD, which makes research much more difficult and has led to many of such promising targets yielding no results.…”
Section: Reviewmentioning
confidence: 97%
“…Especially NE and MMP-9 are targeted, together with neutrophil infiltration. For example, inhibiting PI3Kd decreases neutrophil infiltration in murine models of acute lung damage, and might therefore also be a target for the treatment of COPD [128]. However, it seems that neutrophil signaling pathways are altered in COPD, which makes research much more difficult and has led to many of such promising targets yielding no results.…”
Section: Reviewmentioning
confidence: 97%
“…PI3K γ deficiency could significantly reduce the influx of neutrophils into BALF [52]. PI3K δ inhibition may also prevent recruitment of neutrophils [53]. The PI3K-related inflammation and steroid insensitivity should partly be attributed to microRNA-21/PI3K/histone deacetylase 2 (HDAC2) axis as Kim et al reported [54].…”
Section: Asthmatic Neutrophilsmentioning
confidence: 99%
“…Although TG100-115, PI3Kγ and -δ inhibitor, was proven to be effective in the mouse smoke-induced lung inflammation model (Doukas et al ., 2009), the clinical development has been discontinued at present. Recent study suggested that targeting PI3Kδ was beneficial for the treatment of respiratory diseases (Sriskantharajah et al ., 2013). GSK2269557, an inhaled PI3Kδ inhibitor, is currently undergoing clinical trial for COPD.…”
Section: Currently Developing Drug Candidates For Copdmentioning
confidence: 99%